HUBUNGAN DUKUNGAN KELUARGA TERHADAP MOTIVASI PENDERITA GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISA - ", Mardiana "; ", Erwin "; Dewi, Yulia Irvani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2017)
AbstractChronic renal failure disease (CRF) is included into the top ten non communicable diseases that often occur with a prevalence of 0.2% in Indonesia. The prevalence of CRF is often overlooked, although CRF is a disorder that is chronic and can take place progressively. The purpose of this study was to analyze the relationship of family support and motivation in patients with Chronic Renal Failure a Hemodialysis at Dumai city hospital. The design of study is descriptive corelation with cross sectional approach. The number of samples were 51 respondents based on criteria inclusion. Instrument used in the study was questionnaires that on validity and reliability test. The univariate analysis was conducted to show frequencies distribution and bivariate analysis was conducted by using Chi-Square. The results showed that the majority of patients with chronic renal failure undergoing hemodialysis partially patients with chronic renal failure undergoing hemodialysis have high family support as many as 37 people (72.5%), and most patients with chronic renal failure undergoing hemodialysis have high motivated many as 27 people (52.9%). The results showed that there was correlation between support for families with the motivation of patients with chronic renal failure on hemodialysis room at Dumai City Hospital with p value (0.001). Based on study, it is recommended to family in Hemodialisys unit to give support to increase patient’s motivated for undergoing hemodialysis. Keywords: Family support, Motivation, Chronic Renal Failure (CRF)